Quality of Life Near Nuclear Power Plants (Journal of Universal Excellence, 2026)
Research Question (RQ): "What is the quality of life near nuclear power plants?"Purpose: The purpose and purpose of the research is to explore and determine the quality of life of those living near or near nuclear power plants. Quality of life depends on a number of factors, such as the environment, nuclear accidents, waste and discharges.Method: In the study we used a quantitative method. We've come from known sources. We also used our own experiences from a selected organisation.Results: The results of the study show that nuclear energy is at its lowest point in terms of emissions into the environment. In the past, the operation and consequent radiation of nuclear power plants have caused diseases, especially cancer. Ernest Sternglass found that on the way from Krško to Ljubljana almost doubled the value of radioactivity. We detailed the radioactivity releases for the Krško Nuclear Power Plant. According to the current measurements carried out by the various organisations, NEK is far below the administratively defined restrictions. The better the quality of life, the higher the standard of living.Organisation: The public and those who stay next to nuclear power plants need to understand the benefits and disadvantages of nuclear technology. We must be aware that electricity is urgently needed in this day and age.Society: Researchis an aspect of people's connection, quality to nuclear technology and the environment.Originality: From the literature review we will recognize both the positive and negative effects of nuclear energy. The fact is that materials and equipment are changing and that in this day and age, the installation of newer and better quality equipment is in nuclear facilities.Limitations/Future Research: For a broader view of the quality of life in the vicinity of nuclear power plants, it would make sense to examine in detail all environmental impacts and to expand and integrate social and economic aspects.
Keywords: nuclear power plant; quality of life; environment; nuclear accidents; energy; Krško nuclear power plant